Dual-Effect Moderation Generative AI: Penguatan dan Risiko Dalam Ekosistem Daya Saing Digital UMKM - Tamzil, Fachmi; Praja, Arief Kusuma Among; Amalia, Lia; Sumitro, Dewi Sari (ARBITRASE: Journal of Economics and Accounting, 2025)
This study examines the relationship between digital transformation, technological readiness, and the competitiveness of micro, small, and medium enterprises (MSMEs) in the context of the rapid development of Generative Artificial Intelligence (GenAI). The main problem addressed is the low level of technological readiness among many Indonesian MSMEs, which slows digital adoption and weakens their ability to compete in a technology-driven market. The research focuses on the MSME landscape in Indonesia and employs a literature-based qualitative approach, analyzing more than 40 recent scientific publications relevant to digital transformation and GenAI. Data were interpreted using content analysis to identify recurring conceptual patterns, variable interactions, and the moderating role of GenAI.  The findings indicate that digital transformation and technological readiness are key determinants of MSME competitiveness, primarily through improved efficiency, innovation capacity, and strategic adaptability. Furthermore, GenAI acts as a dual-effect moderator: strengthening the positive influence of digital transformation and technological readiness when strong governance and digital literacy are present, but potentially weakening organizational performance when governance and technological capability are insufficient. The study provides a conceptual foundation for future empirical research and highlights strategic directions for accelerating intelligent technology adoption among MSMEs in the era of generative technologies.